Pengaruh Celebrity Endorser Dan Brand Image Terhadap Keputusan Pembelian Shampoo Clear - Kalangi, Natalia Junni; Tamengkel, Lucky F.; Walangitan, Olivia F. C. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This study aims to determine: (1) the effect of celebrity endorsement on purchasing decisions for Clear brand shampoo, (2) the effect of brand image on purchasing decisions up to Clear brand, and (3) the influence of celebrity endorse and brand image on Clear shampoo shampoo purchase decisions.This study uses a quantitative approach bycollecting data through survey methods. This study also uses a purposive sampling technique based on certain characteristics. The sample in this study were 100 people of the Wenang sub-district of Manado city. Data collection techniques using questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression.The results of this study indicate that: (1) Celebrity endorse has a positive effect on purchasing decisions, evidenced by the value of t count of 2.186 with a significance value of 0.031, smaller than 0.05 and the regression coefficient has a positive value of 0.340; (2) Brand image has a positive effect onpurchasing decisions, evidenced from the value of t count of 4.346 with a significance value of 0,000, smaller than 0.05 and the regression coefficient has a positive value of 0.749, and (3) Celebrity endorsers and brand images have a positive effect against purchasing decisions, as evidenced by the results of F count of 29,446 with a significance of 0,000. The adjusted R square value of 0.378 indicates that the ability of the independent variable in explaining the variation of the dependent variable is 37.80%, and the remaining 62.20% is explained by other variables outside the research model.